Codeposition of Cu-Sn from Ethaline Deep Eutectic Solvent. (20th November 2015) - Ghosh, Swatilekha; Roy, Sudipta
Highlights: First systematic electrochemical study of Cu-Sn co-deposition from a chloline-chloride based DES. Metallic Cu-Sn have been deposited potentiostatic and galvanostatic routes using hydrated salts. Cu-Sn is co-deposited at potentials more noble than the reduction of Sn from the same DES. Homogeneous, dense deposits containing a mostly Cu3 Sn phase of up to 10 um has been obtained. Abstract: Copper and tin have been co-deposited from choline chloride ethylene glycol based deep eutectic solvent (DES) containing CuCl2 .2H2 O and SnCl2 .2H2 O. Initially, electrolyte formulation experiments were carried out containing different amounts of copper and tin at a brass cathode in a rotating cylinder Hull cell. It was found that metallic deposits containing copper and tin could be deposited from a DES containing 0.02 M CuCl2 .2H2 O and 0.1 M SnCl2 .2H2 O. Polarization scans were carried out to determine the reduction potentials for individual metals and alloys. Anodic stripping voltammetry showed that Sn co-deposits with Cu at -0.36 V, at a lower over-potential than the tin reduction potential. Smooth and bright deposits of thicknesses up to 10 μm were obtained at a potential of -0.36 V or by using a current density of −0.87 × 10 −3  A cm −2 . XRD analysis showed the formation of mainly Cu3 Sn and some Cu5 Sn6 . Our results suggest that Sn is co-discharged with Cu at potentials which is noble compared to the reduction potential of the individual metal.